Critérios de sustentabilidade para contratações de obras na administração pública - Silva, Wesley Pereira da (2013)
Objective of this research was to diagnose the influence of establishing criteria, practices and sustainability guidelines for the public procurement of building undertaken by the federal government. This work was conducted through document research and literature. It was found that the literature proposes related to sustainability in construction; correlating the criteria set by the LEED system (Leadership in Energy and Environmental Design) with parameters set by the Brazilian government, and applied to measurement proposed by the LEED system in seven public procurement process. The data analyzed were collected procurement from the procurements information provided on the website of the Instituto Federal do Espírito Santo. The research concluded that the evolution of Brazilian law, in relation to public procurement, demonstrates the concern of the government with national sustainable development. The criteria sustainabilities added to procurement requirements are consistent with the items evaluated in the LEED certification system, but the requirement of a system for measuring the sustainability of construction can ensure proper compliance with the law.